Unconventional Powertrain Simulatiion - Brumercik, Frantisek; Lukac, Michal; Caban, Jacek (Communications - Scientific letters of the University of Zilina, 2016)
This article presents an unconventional principle of the vehicle power flow transmission, different from the commonly used powertrains. Presented powertrain consists of a combined hydro-mechanical transmission with hydrostatic units and torque converter in parallel lines with mechanical components providing the continuous gear ratio change.